CONODONT DATING OF THE LOWER TRIASSIC SEDIMENTARY ROCKS IN THE EXTERNAL DINARIDES (CROATIA AND BOSNIA AND HERZEGOVINA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
Two Lower Triassic sedimentary successions have been dated by means of conodonts in the External Dinarides: Plavno section near Knin, Croatia and Bosansko Grahovo section in Bosnia and Herzegovina. Deposition in both sections shows similar characteristics, differentiated in three continuously deposited facies. The Siliciclastic facies was previously considered Seis beds and assigned to the lower Lower Triassic, the Mudstone facies, and the Siltstone-mudstone facies (occurring in the upper part of the succession) were formerly considered as Campil beds of the upper Lower Triassic. Vertical succession of Siliciclastic, Mudstone, and Siltstone-mudstone facies of both investigated sequences was interpreted as deepening of the environment envisaged as a transgressive trend in a shallow shelf environment. Facies successions at Plavno (690 m thick) and Bosansko Grahovo (229 m thick) differentiate for the presence of Dolostone facies in the lowest part of the Plavno succession. Conodont fauna of Dolostone facies at Plavno section is represented by isarcicellids, Isarcicella staeschei and I. isarcica (sample 3) that marks the Griesbachian isarcica Zone. The Siliciclastic facies of Plavno and Bosansko Grahovo sections is characterized by shallow-water euryhaline taxa attributed to the Smithian, part of the late Dinerian-Smithian obliqua Zone. This fauna is prevailed by Hadrodontina anceps and Pachycladina obliqua with co-occurrence of Smithian Parachirognathus ethingtoni and very rare presence of Foliella sp. or ?Furnishius sp. Discerned conodont taxa enable us to establish conodont zonation which gives new insight to the range of the so-called Siusi and Campil beds.
Keywords: Early Triassic; External Dinarides; Conodont dating; Croatia; Bosnia and Herzegovina